Tindak Pidana Korupsi oleh Pejabat Negara Perspektif Hukum Pidana Politik - Anton Jaksa Trisakti; Pujiyono Pujiyono (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2022)
Political crimes or political criminal law in Indonesia are known in the Criminal Code, namely crimes against state security in Book Two of Chapter I. Meanwhile, the notion of political crime in Indonesia has not been explicitly defined in the legislation, giving rise to a wide understanding of the forms of political crimes. Corruption is a white-collar crime, it is necessary to study from the perspective of political criminal law whether corruption by state officials is a political crime. The purpose of this paper is to see whether a criminal act of corruption is a political crime and how is the punishment of criminal acts of corruption by state officials in the perspective of political criminal law. Normative juridical writing method with a conceptual approach. This study found that corruption by state officials is a political crime according to the categorization of the concept of political crime proposed by Dionysios Spinellis, namely crimes committed by power holders in accordance with Law Number 31 of 1999 concerning Corruption Crimes (UUTPK) Article 3 which states that the crime of corruption is a criminal act committed by a person who with the authority of his position or position is detrimental to state finances or the state economy. The punishment of a state official who commits a political crime, in this case a criminal act of corruption, may be subject to the provisions of Article 3 of the Corruption Crime Act in the form of imprisonment and/or a fine. Kejahatan politik atau hukum pidana politik di Indonesia dikenal dalam KUHP yaitu tindak pidana terhadap keemanan negara pada Buku Kedua Bab I. Sedangkan pengertian kejahatan politik di Indonesia belum didefiniskan secara eksplisit dalam perundang-undangan sehingga menimbulkan pemahaman yang begitu banyak mengenai bentuk dari kejahatan politik. Tindak Pidana Korupsi merupakan kejahatan kerah putih, maka perlu dikaji dari perspektif hukum pidana politik apakah kejatan korupsi oleh pejabat negara merupakn kejahatan politik. Tujuan penulisan ini untuk melihat apakah suatu tindak pidana korupsi merupakan kejahatan politik dan bagaimana pemidanaan terhadap tindak pidana korupsi oleh pejabat negara dalam perspektif hukum pidana politik. Metode penulisan yuridis normatif dengan pendekatan konseptual. Penelitian ini menemukan bahwa korupsi oleh pejabat negara merupakan kejahatan politik sesuai ketegorisasi konsep kejahatan politik yang dikemukan Dionysios Spinellis, yaitu kejahatan dilakukan pemegang kekuasaan sesuai dalam Undang-Undang Nomor 31 Tahun 1999 tentang Tindak Pidana Korupsi (UUTPK) Pasal 3 yang berbunyi bahwa tindak pidana korupsi merupakan suatu tindak pidana yang dilakukan oleh seseorang yang dengan kewenangan jabatan atau kedudukannya merugikan keuangan negara atau perekonomian negara. Pemidanaan terhadap pejabat negara yang melakukan tindak pidana politik dalam hal ini tindak pidana korupsi dapat dikenakan ketentuan Pasal 3 Undang-Undang Tindak Pidana Korupsi berupa pidana penjara dan/atau pidana denda.